Proteinuria and malaria parasite counts in children - Mahrani Lubis; Rusdidjas Rusdidjas; Rafita Ramayati; Oke Rina Ramayani; Rosmayanti S Siregar; Supriatmo Supriatmo (Indonesian Pediatric Society Publishing House, 2013)
Background Malaria-induced proteinuria has been observed in severe cases of malaria. Few studies have been done to assess for an association between proteinuria and malaria parasite counts before the disease becomes severe. Objective To investigate a possible association between proteinuria and malaria parasite counts in children . Methods A cross-sectional study was conducted on school-aged children in Panyabungan, Mandailing Natal, between September to November 2010. Malaria was diagnosed by microscopic examination of peripheral blood smears. Children with malaria underwent proteinuria t ests by urine dipstick method. An association between proteinuria and malaria parasite counts was analyzed using linear regression test. Results Of 181 participants with Plasmodium fak:iparum malaria, 53.6% were female and had a mean age of 7.8 years. Subjects' nutritional status were as follows: 50.8% normoweight, 28.2% mild malnutrition, 3 .3% moderate malnutrition, and 17. 7% severe malnutrition. Clinical manifestations showed 36.5% suffered from subfebrile temperatures and 29.8% had pallor. Proteinuria occurred in 45.9% participants and there was a weak association between proteinuria and malaria parasite counts (raa .261, Paa .0001). Conclusion There is a weak association between proteinuria and malaria parasite counts in children.